16. CHARACTERISTICS OF BLOOD FORMULA, CYSTOLOGY AND BONE MARROW HISTOPATHOLOGY RESULTS OF PATIENTS WITH BLOOD DISEASES TREATED AT HONG AN GENERAL FRIENDSHIP HOSPITAL IN THE PERIOD OF 2023-2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics of complete blood count, bone marrow cytology, and histopathology results in patients with hematologic diseases treated at Nghe An General Friendship Hospital during the period 2023-2024.Subjects and methods: A cross-sectional descriptive study was conducted on 874 patients who underwent initial testing, including complete blood count, bone marrow cytology, and/or histopathology, at Nghe An General Friendship Hospital from June 2023 to May 2024.Results: The mean age of patients was 77.5 years, with an equal distribution between males and females. Most patients were from the Department of Clinical Hematology. In some cases, bone marrow cytology alone was insufficient to comprehensively assess bone marrow characteristics. The combination with bone marrow histopathology provided additional information on microstructure and hematopoietic cell density, thereby improving diagnostic accuracy. Normal marrow cellularity on histopathological specimens accounted for the majority (73.6%), with discrepancies observed between cytological and histopathological findings. Bone marrow histopathology was considered more reliable and objective.Conclusion: Combining bone marrow cytology and histopathology offers a more comprehensive assessment of the hematopoietic environment, thereby enhancing the accuracy of diagnosing hematologic diseases.
Keywords: Hematology, cytology, histopathology, bone marrow.